Towards Automatic Generation of Application Ontologies - Sacramento, Eveline R.; Vidal, Vânia M. P.; Macêdo, José Antonio F. de; Lóscio, Bernadette F.; Lopes, Fernanda Lígia R.; Casanova, Marco A. (Journal of Information and Data Management, 2010)
In the context of the Semantic Web, a domain ontology may be used to provide the necessary support for linking together a large number of heterogeneous data sources pertaining to a same domain. In this paper, such data sources are ?rst described as local ontologies. Then, each local ontology is rewritten as an application ontology, whose vocabulary is restricted to be a subset of the vocabulary of the domain ontology. Application ontologies enable the identi?cation and the association of semantically corresponding concepts, and thereby help information discovery and retrieval, and also data integration. The main contribution of this paper is a strategy to automatically generate application ontologies, considering a set of local ontologies, a domain ontology and the result of the matching between each local ontology and the domain ontology. The proposed strategy also enables the automatic generation of mappings between the domain ontology and the application ontologies, and between each application ontology and its corresponding local ontology, which are used to query the data sources through the domain ontology.